CASE REPORT Management Cataract Complication and Malignant Glaucoma After Viterectomy Surgery and C3F8 Gas Tamponnade - Frisma Sagara Brilliyanto; Wimbo Sasono (Jurnal SainHealth, 2020)
Report a clinical presentation of patient with rhematogenous retinal detachment by viterectomy and high myopia with C3F8 gas tamponade. A 20-year-old female came into the outpatient clinic with blurry vision on the right eye as her chief complaint. It had been happening since 1 month ago. In examination, we found result of visual acuity RE 1/300 and LE 1/60 correction Sferis-16.00 5/7.5, anterior segment in a normal range. In posterior segment evaluation, there were RE detachment on 3-11 o’clock position and hole on 6 and 8 o’clock position. Then we performed vitrectomy and  C3F8 gas tamponade. The first day after surgery, we found IOP 19,6 mmHg and Von Herrick III. Then after the second day, we found a pain on the right eye, TIO 47.3 mmHg, Von Herrick 0 and opaque lens. Then we performed iridectomy and intravitreal gas aspiration. After it were done, we found IOP 17.3 mmHg and Von Herrick 0. In anterior segment OCT evaluation, we found a narrow angle anterior segment. Then we planned to do a cataract extraction with using viscoelastic to perform the anterior chamber.Malignant glaucoma can occur in cases after vitrectomy action due to aqueous misdirection and emphasis on gas expansion on tamponade. Cataract extraction and gas aspiration can help open the anterior chamber and the intraocular pressure returns to normal